Diet and foraging behaviour of Macaroni and Chinstrap penguins at Bouvetøya, South Atlantic Ocean - Huyser, Onno Adrian Wallace (Percy FitzPatrick Institute of African Ornithology, 2014)
Bibliography: leaf 195.